Is Olea ferruginea (Indian Olive) Inferior to Olea europaea (Common Olive) in Olive Oil Content? - Joshi, S. C.; Bhardwaj, V. (Indian Forester, 2015)
Olive oil is highly valued vegetable oil in the world over because of its nutritional and medicinal qualities. Various efforts including introduction of Olea europaea and its cultivars to various other parts of the world suitable for their cultivation are being made to meet increasing demand for olive oil. Olea ferruginea Royle, locally known as Kahu in north west Himalaya and Bairbanj in Garhwal Himalaya, is a multipurpose, zero waste evergreen tree species as it yields a number of useful items including quality fodder, fuelwood, timber, and has medicinal properties. The present study was undertaken to find out whether or not O. ferruginea could be used as a source of olive oil. Four populations of O. ferruginea (Kolibehar, Saioond and Kais) from Kullu district and (Thalaut) from Mandi district were selected as the sources of fruits and seeds. The olive oil contents in the fruits varied from 20.00% to 27.40%, and the oil content was maximum in the fruits of Thalaut population and minimum in the Kolibehar population. The olive oil content in the seeds varied from 7.50% to 12.50%; the oil content was the highest in the seeds of the Thalaut population and the lowest in the Saioond population. The fatty acid composition of the fruit oil showed that the oil is rich in monounsaturated fatty acids (range 63-68%) and unsaturated fatty acids (range 79-84%) and poor in polyunsaturated fatty acids (range 14-17%) and saturated fatty acids (range 16-21%). These values are similar to those reported for wild populations and various other cultivars of O. europaea. Based on the oil content data it may be suggested that the fruits of O. ferruginea may be a potential source of olive oil.